A double-blinded, randomized, vehicle-controlled study to access skin tolerability and efficacy of an anti-inflammatory moisturizer in treatment of acne with 0.1% adapalene gel - Chularojanamontri, Leena; Tuchinda, Papapit; Kulthanan, Kanokvalai; Varothai, Supenya; Winayanuwattikun, Waranaree (The Journal of dermatological treatment, 2016)
Introduction: Topical retinoids are considered to be the first-line agents and maintenance therapy of acne; however, irritation side effects are major concern issues. Noncomedogenic moisturizers are sometimes added to relieve cutaneous irritations. This study aimed to compare tolerability and efficacy of moisturizers containing licochalcone A, l-carnitine and 1,2-decanediol (active formulation) with a placebo in mild to moderate severe acne in Asian subjects. Methods: This was an 8-week double-blind, prospective, randomized controlled study. All patients (n = 120) were randomized equally into three groups: (A) adapalene gel, (B) adapalene gel with the active formulation and (C) adapalene gel with the placebo. The severity of acne, skin bioengineering measurements and skin tolerability were recorded during the study. Results: Compared to baseline, the active formulation group showed significant reductions in inflammatory lesions and total lesions at the end of the study without flare-up. Moreover, skin irritations were less detected than in the other two groups by corneometer and transepidermal water loss measurements. Conclusions: The concomitant usage of adapalene gel and the moisturizer containing licochalcone A, l-carnitine and 1,2-decanediol could reduce undesirable side effects without interfering the efficacy of adapalene. This moisturizer may be superior to placebo to prevent cutaneous irritations and enhance patients' adherence to acne medications.